Analisis Makna Upacara Tolak Balak di Desa Talang Tengah II Kecamatan Pematang Tiga Kabupaten Bengkulu Tengah - Zulyan Zulyan; Muslih Hasibuan (Equilibrium: Jurnal Pendidikan, 2022)
Tradition is a habit of a group of people that is passed down from generation to generation, in which it contains the value of trust from the community itself. Each region has have different traditions, this shows that the Indonesian people are rich in culture, so the problem to be studied in this study is the analysis of the meaning of the rejection ceremony in Talang Tengah II village, Pematang Tiga District, Central Bengkulu Regency. In this study, a qualitative research method was used to describe the data regarding the ritual of the rejection ceremony in Talang Tengah II Village. To obtain correct information and data, the data collection technique in this study was carried out through interviews and direct observation of this ritual process. The validity of the data is checked, then the presentation and analysis of the data is carried out and then conclusions are drawn. The results of this study show that (1) The ritual of rejecting balance in Talang Tenga II Village has positive values, namely the value of trust, the value of togetherness and care for the environment. (2) The process of the rejection ceremony ritual is carried out at the village elder's house and led by a village elder who is trusted by the community, while the ritual equipment is prepared by the village maidens and the results of this ritual are distributed to the local community to be sprinkled on vehicles, plants and farm animals. (3) The form of preservation of the ritual of rejecting balance in Talang Tengah II village is carried out every year at the end of the year so that this tradition is maintained to this day.